2019
DOI: 10.1167/iovs.18-24935
|View full text |Cite
|
Sign up to set email alerts
|

A New Ophthalmic Pharmaceutical Formulation, Topical Sulglycotide, Enhances the Ocular Mucin Secretion in Desiccation Stress-Mediated Dry Eye Disease

Abstract: The aim of this study was the investigation of the effect of sulglycotide (SOS), a polysulfated glycopeptide derived from porcine duodenal mucin, for the treatment of dry eye disease. METHODS. NOD.B10.H2 b mice were exposed to an air draft for 10 days, and, simultaneously, scopolamine hydrobromide was injected subcutaneously. The mice were randomly divided into nine groups as follows: four kinds of SOS formulations and three kinds of commercial medicine. After 10 days of treatment, we estimated the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“… 36 In previous studies, DS was found to upregulate the expression of inflammatory markers and the infiltration of immune cells in the lacrimal gland. 24 , 37 Likewise, in the present study, DS resulted in infiltration of inflammatory cells and abnormal acini in the lacrimal gland, with increased infiltration of F4/80 + macrophages and CD4 + T cells. In addition, DS led to overexpression of pro-inflammatory cytokines in the lacrimal gland.…”
Section: Discussionsupporting
confidence: 74%
“… 36 In previous studies, DS was found to upregulate the expression of inflammatory markers and the infiltration of immune cells in the lacrimal gland. 24 , 37 Likewise, in the present study, DS resulted in infiltration of inflammatory cells and abnormal acini in the lacrimal gland, with increased infiltration of F4/80 + macrophages and CD4 + T cells. In addition, DS led to overexpression of pro-inflammatory cytokines in the lacrimal gland.…”
Section: Discussionsupporting
confidence: 74%
“…Dysfunction of the lacrimal function unit (LFU) alters the tear film composition, breaks ocular surface homeostasis and facilitates ocular surface inflammation 4 . Goblet cells and mucins are important components of LFU 30 . In line with other reports, our study revealed that chronic desiccating stress cause loss of goblet cell density and reduced expression of MUC-1 and MUC-5AC, while significantly improved by topical application of hADSC-Evs eye drops, indicating that hADSC-Evs protect ocular surface against desiccating stress via restoring normal tear film.…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of 0.01% Lacripep TM in mice DES model was found to result in 46% increase in tear secretion and reduction in lissamine green staining, and to recovery of the expression of corneal-specific cytokeratin K12, which is prevalent in the healthy ocular mucosal epithelium [76,80]. An emerging substance which has shown therapeutic promise when topically instilled in mice dry eyes is sulglycotide, a polysulfated glycopeptide derived from porcine duodenal mucin, which among others induced an increase in the numbers of goblet cells and enhanced the expression of MAM (MUC1, MUC4, and MUC16) and of the gel-forming mucin, MUC5AC [81].…”
Section: Discussionmentioning
confidence: 99%